Seven pillows of wisdom - ACTT leaflet, 1965 (London, 1965)
1965 1961-70 "Seven pillows of wisdom - ACTT leaflet, 1965" [BW0141], 1965, Trades Union Congress This leaflet probably dates from the union organisation campaign in Kodak in 1965. Unions were not recognised at the American owned Kodak company until 1972, when the Union of Kodak Workers replaced the workers' representation committees, which themselves had superseded wartime production committees. The Association of Cinematograph, Television and Allied Technicians finally obtained union recognition at Kodak in January 1974 after another 3 months strike. The UKW merged with the Transport and General Workers Union in 1974.